Barium uptake by maize plants as affected by sewage sludge in a long-term field study - Rodrigues Nogueira, Thiago Assis; deMelo, Wanderley Jose [UNESP]; Fonseca, Ivana Machado [UNESP]; Marques, Marcos Omir [UNESP]; He, Zhenli (Elsevier B.V., 2010)
Along-term experiment was carried out under field conditions in Jaboticabal, SP, Brazil, with the objective of evaluating the concentration of Ba in soil and in maize plants grown in a soil treated with sewage sludge for nine consecutive years. During 2005/2006, maize was used as test plants and the experimental design was in randomized complete blocks with four treatments and five replicates. Treatments consisted of: 0.0, 45.0, 90.0 and 127.5 t ha(-1) sewage sludge (dry basis). Sewage sludge application increased soil Ba concentration. Barium accumulated in the parts of maize plants were generally affected by the successive applications of sewage sludge to the soil. However, the concentration of Ba in maize grain did not exceed the critical levels of Ba for human consumption. Sewage sludge applied to soil for a long time did not affect dry matter and grain production, nevertheless had the similar effect of mineral fertilization. Published by Elsevier B.V.
Keywords: Zea mays L.; biosolid; Heavy metal; Urban waste; Food contamination